British Labour delegation to Russia, 1920 (1920)
1920 1918-1939 "British Labour delegation to Russia, 1920" [T0292.jpg], 1920 The delegation comprised Ben Turner, Ethel Snowden, Tom Shaw and Robert Williams from the Labour Party; Margaret Bondfield, A.A. Purcell and H. Skinner from the TUC. The joint secretaries to the delegation were Charles Roden Buxton and L. Haden Guest. R.C. Wallhead and Clifford Allen from the Independent Labour Party accompanied the delegation.